Associativism in Contemporary Brazil: Institutional and Individual Dimensions - Lígia Helena Hahn Lüchmann; Carla Almeida; Luana do Rocio Taborda (Política & Sociedade, 2018)
This article analyzes continuities and changes in the patterns of associative participation in Brazil from two analytical perspectives: the dimension related to the volume and characteristics of the associative tissue, and the dimension of the size of the individual’s engagement in associations. The first presents the recent evolution of associativism in the country, measured by the quantity, profile and scope of associations. In the second, the evolution of participation on the level of individual engagement is considered through the assessment of the number of individuals who claim to take part in associations. This assessment is based on public opinion research data from the World Values Survey project and from Fundações Privadas e Associações Sem Fins Lucrativos no Brasil (FASFIL)/Instituto Brasileiro de Geografia e Estatística (IBGE) and Profile of Social Society Organizations of Instituto de Pesquisa Econômica Aplicada (IPEA) reports. The data allows for the suggestion that, in the last decades, Brazil witnessed an important growth of associations founded – reflected in the greater internal diversification of this universe – while the number of engaged individuals did not follow this evolutionary growth. We suggest that the expansion of associativism was only selectively reflected in the level of individual engagement, and that the specific profile of associations that found growth-enhancing territory in the period, of a more professional nature, helps to understand the difference pointed out in the two dimensions.